An Examination of the Relationship Between Firm Characteristics and Financial Reporting Quality - Okei Bukky Peace (Journal of Accounting, Finance, and FinTech Advancements, 2025)
This research delves into how the qualities of companies are connected to the accuracy of financial reporting in consumer goods companies in Nigeria that are publicly traded. By using data from financial documents from 12 consumer goods companies in Nigeria from years 2014 to 2023, the study looked at three different aspects of companies (firm size, board makeup, and profitability) to see how they relate to the quality of financial reporting. The accuracy of financial reporting was assessed in the research using the Modified Jones Model. The data was examined using a combination of basic statistics, tests for issues, and advanced statistics. The research established a straight line pattern which was evaluated using a basic analysis of regression. It was discovered that the makeup of a board greatly affects how well consumer goods companies report their finances in Nigeria. Conversely, the size and profitability of a company do not have much impact on the quality of financial reporting for consumer goods companies in Nigeria. The results showed that when taken together, the various characteristics of companies studied in this research are significantly linked to the quality of financial reporting for public consumer goods companies in Nigeria. Based on these findings, the research recommended that businesses should work on setting up strong internal controls, reliable reporting channels, and appropriate structures for governance to deal with the negative consequences of these factors.